Satisfying higher education students’ psychological needs through case-based instruction for fostering creativity and entrepreneurship - Xiaojing Weng; Qi Xia; Thomas K. F. Chiu; Zhihong Wan (Humanities & Social Sciences Communications)
Abstract Designing effective strategies for developing higher education students’ competencies, such as creativity and entrepreneurship, is crucial for their survival and self-realization in the technology-rich 21st century. This study is important as it addresses a significant research gap by designing and implementing self-determination theory (SDT)-guided case-based instruction (CBI) to enhance digital learners’ creativity and entrepreneurship. A class of 34 master’s students in a taught programme focused on digital learning and technology at a public university in Hong Kong participated in the study. First, the students took a pre-test to assess their creativity and entrepreneurship. They then experienced a 13-week course designed using SDT-guided CBI. After the intervention, they completed a post-test on their creativity and entrepreneurship. Additionally, the researchers conducted interviews with 10 participants. These processes allowed the researchers to evaluate the effectiveness of the SDT-guided CBI learning activities and to gather participants’ suggestions for improving the design. The results of a repeated measures analysis of variance indicated the feasibility of SDT-guided CBI. Significant improvements in creativity were observed from the pre-test to the post-test, from the pre-test to the mid-test, and from the mid-test to the post-test. Meanwhile, students’ entrepreneurship significantly increased from the pre-test to the post-test, although the increases from the pre-test to the mid-test and from the mid-test to the post-test were slight and did not reach a significant level. From the qualitative data, students provided suggestions such as selecting effective case studies, using entrepreneurs’ stories, supporting entrepreneurial experiences, promoting technology-enhanced learning, and advocating for collaborative learning to improve the design. The findings imply that SDT-guided CBI has the potential to continually enhance students’ creativity and entrepreneurship throughout its implementation, with significant opportunities for improvement based on the implementation experiences.